DETERMINAN STATUS ANEMIA SISWA SLTA DI DKI JAKARTA - Fitrah Ernawati; M. Saidin (Persagi, 2008)
Determinants of Anemia Status Among High School Students In Jakarta.Background: The prevalence of anemia among adolescents remains high. The effect of anemia among adolescents especially girls will affect the health status of mothers in the future.Objectives: The study was to analyse the determinants of anemia status among adolescents high school students.Methods: The study design was crosssectional from The Survey Of School Children's Nutritional Status at 10 Cities In Indonesia 2005. The samples of the study were adolescent aged of 15-19 years from high school in Jakarta.Results: The result of the study was that anemia among adolescents high school students were 16%, and the female students had 2.2 (Cl 95%: 1.3-3.7) risk of getting anemia compared to male students.Conclution: Adolescents high school female students need more attention because they have twice the chance to get anemia than male.Keyword: status anemia, female students, high school students